Comparing Absorbable and Nonabsorbable Sutures in Corporeal Plication for Treatment of Congenital Penile Curvature - Basiri, Abbas; Sarhangnejad, Reza; Ghahestani, Seyyed Mohammad; Radfar, Mohammad Hadi (Urology Journal, 2011)
Purpose: To compare the outcome of corporeal plication using absorbable versus nonabsorbable sutures for the treatment of congenital penile curvature. Materials and Methods: Thirty-eight men older than 15 years old with congenital penile curvature were enrolled in the study. Patients were randomly divided into two equal groups based on the suture material (Nylon versus Vicryl) used in corporeal plication. Patients were followed up for a mean period of 8.1 ± 1.4 months (range, 6 to 9.1 months). A standardized questionnaire was used to evaluate long-term outcome and patient’s satisfaction. Results: Thirty-five patients (17 in Vicryl group and 18 in Nylon group) completed the study. Mean age of the patients and degree of penile curvature were not significantly different between the two groups (P = .74). Postoperatively, 15 (88.2%) and 16 (88.9%) patients in Vicryl and Nylon groups had 75% or greater correction in penile curvature, respectively (P = .61). Patient’s satisfaction rate differed between two groups (82% in Vicryl group versus 66% in Nylon group), which did not reach statistical significance (P = .44). Palpable sutures were reported by 7 (39%) patients in Nylon group and only 1 (6%) in Vicryl group (P = .04). Shortening of penile length was reported by 3 (16.7%) patients in Nylon group and 4 (23.5%) in Vicryl group (P = .69). Conclusion: Corporeal plication technique using absorbable suture provides reasonable success rate with less frequent palpable suture knots.